Ensaio de imunoabsorção enzimática (ELISA) IgG indireto in-house com a proteína recombinante LipL32 para detecção de anticorpos anti-Leptospira spp. em soro canino - Lansarin, Taynara Dias (2025)
Leptospirosis is an infectious disease zoonotic and distributed worldwide, caused by bacteria of the genus Leptospira. The infection is predominantly acquired through direct contact with the urine of infected animals or, indirectly, through contact with contaminated environments (soil and water) or fomites. Dogs, in addition to being infected by the etiological agent and may present important clinical signs, are relevant in the epidemiological chain of the disease, as they can be considered sentinels, reservoirs and transmit the pathogenic agent to other susceptible individuals. The gold standard test to diagnose the infection is the microscopic seroagglutination test (MAT), an indirect methodology based on the detection of antibodies, primarily immunoglobulin (Ig) M. As limitations, the MAT is a subjective, laborious analysis, requires the maintenance of live antigens, specialized technicians and laboratories, and does not differentiate between IgM and IgG antibodies. Thus, the objective of the present study was to standardize and validate an In-house indirect IgG enzyme-linked immunosorbent assay (ELISA) using the recombinant protein LipL32 to detect pathogenic anti-Leptospira spp. antibodies in canine sera. A total of 118 dog serum samples were evaluated by MAT and ELISA, obtaining an accuracy of 78%, sensitivity of 70.6% and specificity of 81%, demonstrating the capacity of this ELISA for use in the diagnosis of canine leptospirosis, as a test screening, as well as in research to evaluate the post-vaccination immune response.